(untitled) (Journal of Pharma Insights and Research, 2026)
Oxidative stress triggers cellular damage via reactive oxygen species, necessitating the search for plant-derived antioxidants to mitigate degenerative pathologies. Clitoria ternatea L., commonly known as butterfly pea, is a valuable source of bioactive metabolites with therapeutic potential. This investigation involved the preparation of aqueous (WEC) and ethanolic (EEC) extracts from dried flowers using ultrasonic-assisted maceration techniques. Preliminary phytochemical screening indicated the presence of flavonoids and saponins in both extracts, while terpenoids were uniquely identified in the aqueous fraction. Quantitative analysis of total flavonoid content revealed higher concentrations in WEC (7.804 ± 0.08 mg QE/g) compared to EEC (3.722 ± 0.01 mg QE/g). Antioxidant capacity was evaluated through the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. The results demonstrated that the aqueous extract possesses superior radical neutralizing capability with an IC₅₀ value of 86.67 ± 0.485 ppm, whereas the ethanolic extract yielded an IC₅₀ of 113.31 ± 0.142 ppm. Quercetin, used as the reference standard, exhibited an IC₅₀ of 22.056 ± 0.196 ppm. The significant activity in the aqueous medium correlates with the higher concentration of polar flavonoids and anthocyanins. Differential solvent polarity dictates the extraction efficiency of these secondary metabolites, positioning the aqueous extract as a more potent candidate for therapeutic applications. The observed radical scavenging properties prove the traditional use of these flowers in health-promoting infusions and natural food colorants.